Factors associated with the opposition to COVID-19 vaccination certificates: A multi-country observational study from Asia. Issue 48 (July 2022) - KC, Sarin; Faradiba, Dian; Sittimart, Manit; Isaranuwatchai, Wanrudee; Ananthakrishnan, Aparna; Rachatan, Chayapat; Dabak, Saudamini; Shafie, Asrul Akmal; Guerrero, Anna Melissa; Suwantika, Auliya; Kang, Gagandeep; Ahn, Jeonghoon; et al.
Abstract: Background: There are ongoing calls to harmonise and increase the use of COVID-19 vaccination certificates (CVCs) in Asia. Identifying groups in Asian societies who oppose CVCs and understanding their reasons can help formulate an effective CVCs policy in the region. However, no formal studies have explored this issue in Asia. Method: The COVID-19 Vaccination Policy Research and Decision-Support Initiative in Asia (CORESIA) was established to address policy questions related to CVCs. An online cross-sectional survey was conducted from June to October 2021 in nine Asian countries. Multivariable logistical regression analyses were performed to identify potential opposers of CVCs. Results: Six groups were identified as potential opposers of CVCs: (i) unvaccinated (Odd Ratio (OR): 2.01, 95% Confidence Interval (CI): 1.65-2.46); vaccine hesitant and those without access to COVID-19 vaccines; (ii) those not wanting existing NPIs to continue (OR: 2.97, 95% CI: 2.51-3.53); (iii) those with low level of trust in governments (OR: 1.25, 95% CI: 1.02-2.52); (iv) those without travel plans (OR: 1.58, 95% CI: 1.31-1.90); (v) those expecting no financial gains from CVCs (OR: 2.35, 95% CI: 1.98-2.78); and (vi) those disagreeing to use CVCs for employment, education, events, hospitality, and domestic travel. Conclusions: Addressing recurring public health bottlenecks such as vaccine hesitancy and equitable access, adherence to policies, public trust, and changing the narrative from 'societal-benefit' to 'personal-benefit' may be necessary and may help increase wider adoption of CVCs in Asia.